Diagnosis of Phase F Student Misconceptions on Newton's Laws: A Case Study in the Merdeka Curriculum - Suban, Maria Enjelina; Mole, Paulina Nelce; Yeyen, Yustina Yesisanita; Early, Indira (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2023)
The current implementation of the Merdeka Curriculum is significantly different from previous curricula. The goal of the Merdeka Curriculum is to focus learning more on achieving understanding of knowledge. Regardless of how frequently learning occurs, the essence is that students must grasp physical and mathematical concepts. Therefore, this study aims to describe students' misconceptions about Newton's Laws. Newton's Laws are foundational concepts in studying dynamics of motion in Phase F. The sample for this study consists of 10 Phase F students from a private school in East Nusa Tenggara, who were given a three-tier diagnostic test. The method used is a survey method. The results indicate that overall, for all Newton's Laws concepts, all students exhibited misconceptions. Many students had misconceptions about Newton's first law as well as concepts of deceleration and friction, with a prevalence of 40%.